2022
DOI: 10.1155/2022/1027288
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Signal‐Crosstalk Mechanism in Maize Plants during Combined Salinity and Boron Stress Using Integrative Systems Biology Approaches

Abstract: Combined stress has been seen as a major threat to world agriculture production. Maize is one of the leading cereal crops of the world due to its wide spectrum of growth conditions and is moderately sensitive to salt stress. A saline soil environment is a major factor that hinders its growth and overall yield and causes an increase in the concentration of micronutrients like boron, leading to excess over the requirement of the plant. Boron toxicity combined with salinity has been reported to be a serious threa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 114 publications
0
2
0
Order By: Relevance
“…Maize is known to be a moderately sensitive cereal crop to salinity (with a threshold salinity of 5 dS/m) which is a major environmental constraint hindering maize production with a grain loss of about 11% [ 8 , 26 ]. Germination rate and growth characteristics may be hindered by the hyperosmotic stress conditions induced by salinity leading to reduced overall yield [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Maize is known to be a moderately sensitive cereal crop to salinity (with a threshold salinity of 5 dS/m) which is a major environmental constraint hindering maize production with a grain loss of about 11% [ 8 , 26 ]. Germination rate and growth characteristics may be hindered by the hyperosmotic stress conditions induced by salinity leading to reduced overall yield [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been found that their expression were induced by silicon (Khan et al 2020 ), ascorbic acid exogenous application (Elkelish et al 2020 ), excessive light and UV-rays (Kim et al 2021 b ), as well as by the humic acid levels raise on soil (Cha et al 2020 ). Furthermore, they are regulated by a series of transcription factors (TFs) (Barua et al 2022 ). In some cereals, the expression was also increased in thermo-conditioning processes (Kushawaha et al 2021 ) and after exposure to thermal, water or saline stress, beyond the heavy metals accumulation (Chaudhary et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%